CONSCIOUS LEADERSHIP AND ITS IMPACT ON REDUCING JOB WITHDRAWAL BEHAVIORS: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF UNIVERSITY LEADERS IN THE FACULTIES OF WARITH AL-ANBIYA UNIVERSITY - Dr. Mohammed Jabbar Hadi; Hussein Sabih Muhaisen (Scholars Digest Publishing, 2024)
The research aims to measure the extent of awareness of conscious leadership and its role in reducing the career withdrawal behaviors of department managers in the food industries company. The research also revealed the importance of a conscious leader in modern leadership styles that take care of the psychological and social factors of individuals and provide them with an incubating environment that enhances their creativity and innovations. To achieve the goals that productive institutions aspire to optimally, the research problem was defined by many questions represented by the nature of the correlation and influence relationships between the research variables and to ensure the validity of the hypotheses. All of them were subjected to multiple tests and the researcher used a questionnaire form to obtain data and information, and the descriptive analytical approach was used. Managers in the food industries company represented the research community, and (80) questionnaire forms were distributed, (78) questionnaire forms were returned, and the valid ones for analysis were (78), i.e. 98% of the sample studied. The researcher used a set of statistical methods, including the SSPS25 program (which is Through processing data and extracting results; one of the most prominent conclusions is that there is a significant role for conscious leaders in reducing job withdrawal behaviours. The research recommended increasing attention to the conscious leadership style and preparing a conscious leader who supports supporting subordinates, taking care of their interests and developing their skills to overcome the obstacles they face at work to achieve the organization’s goals. Efficiently and effectively.
Keywords: Conscious leadership , job withdraw behaviors.